Combination of a new ultrasonic tip with rotary systems for the preparation of flattened root canals - Karina Ines Medina Carita Tavares; Jáder Camilo Pinto; Airton Oliveira Santos-Junior; Fernanda Ferrari Esteves Torres; Juliane Maria Guerreiro-Tanomaru; Mario Tanomaru-Filho (Restorative Dentistry & Endodontics)
ObjectivesThis study evaluated 2 nickel-titanium rotary systems and a complementary protocol with an ultrasonic tip and a small-diameter instrument in flattened root canals.Materials and MethodsThirty-two human maxillary second premolars with flattened canals (buccolingual diameter ≥4 times larger than the mesiodistal diameter) at 9 mm from the radiographic apex were selected. The root canals were prepared by ProDesign Logic (PDL) 30/0.01 and 30/0.05 or Hyflex EDM (HEDM) 10/0.05 and 25/0.08 (n = 16), followed by application of the Flatsonic ultrasonic tip in the cervical and middle thirds and a PDL 25/0.03 file in the apical third (FPDL). The teeth were scanned using micro-computed tomography before and after the procedures. The percentage of volume increase, debris, and uninstrumented surface area were analyzed using the Kruskal-Wallis, Dunn, Wilcoxon, analysis of variance/Tukey, and paired and unpaired t-tests (α = 0.05).ResultsNo significant difference was found in the volume increase and uninstrumented surface area between PDL and HEDM (p > 0.05). PDL had a higher percentage of debris than HEDM in the middle and apical thirds (p < 0.05). The FPDL protocol resulted in less debris and uninstrumented surface area for PDL and HEDM (p < 0.05). This protocol, with HEDM, reduced debris in the middle and apical thirds and uninstrumented surface area in the apical third (p < 0.05).ConclusionsHigh percentages of debris and uninstrumented surface area were observed after preparation of flattened root canals. The HEDM, Flatsonic tip, and 25/0.03 instrument protocol enhanced cleaning in flattened root canals.